2022
DOI: 10.3389/fnetp.2022.817524
|View full text |Cite
|
Sign up to set email alerts
|

Spike-Timing-Dependent Plasticity Mediated by Dopamine and its Role in Parkinson’s Disease Pathophysiology

Abstract: Parkinson’s disease (PD) is a multi-systemic neurodegenerative brain disorder. Motor symptoms of PD are linked to the significant dopamine (DA) loss in substantia nigra pars compacta (SNc) followed by basal ganglia (BG) circuit dysfunction. Increasing experimental and computational evidence indicates that (synaptic) plasticity plays a key role in the emergence of PD-related pathological changes following DA loss. Spike-timing-dependent plasticity (STDP) mediated by DA provides a mechanistic model for synaptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 169 publications
(367 reference statements)
0
38
0
Order By: Relevance
“…Abnormal strengthening of GPe-STN synapses was experimentally attributed to motor cortical-driven heterosynaptic long-term potentiation (hLTP) resulted from interactions between the hyperdirect and indirect pathways ( Chu et al, 2015 , 2017 ). However, findings in animal PD models have revealed that the knockdown of STN NMDARs prevents the strengthening of GPe-STN synapses ( Chu et al, 2015 ), suggesting that classical NMDAR-dependent LTP may be involved in this process ( Madadi Asl et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Abnormal strengthening of GPe-STN synapses was experimentally attributed to motor cortical-driven heterosynaptic long-term potentiation (hLTP) resulted from interactions between the hyperdirect and indirect pathways ( Chu et al, 2015 , 2017 ). However, findings in animal PD models have revealed that the knockdown of STN NMDARs prevents the strengthening of GPe-STN synapses ( Chu et al, 2015 ), suggesting that classical NMDAR-dependent LTP may be involved in this process ( Madadi Asl et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, both the cortex-striatum-GPe-STN and cortex-STN inputs were simply simulated as constant currents and there was no interactions between the BG, cortex and thalamus. Our model may not be able to capture the complex network interactions within the cortico-BG-thalamic circuits leading to pathological structure and dynamics in PD ( Madadi Asl et al, 2022 ), but still can reproduce fundamental biophysical mechanisms related to pathological activity-connectivity patterns in the GPe-STN network, which is considered as the main rhythmogenesis center within the cortico-BG-thalamic network ( Plenz and Kital, 1999 ; Bevan et al, 2002 ; Holgado et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations